Pan-African granulites of central Dronning Maud Land and Mozambique: a comparison within the East-African-Antarctic orogen - Engvik, Ane K; Elvevold, Synnøve; Jacobs, Joachim; Tveten, E; de Azevedo, S; Njange, F (Antarctica - a keystone in a changing world: online proceedings for the 10th International Symposium on Antarctic Earth Sciences, 2007)
Granulite-facies metamorphism is extensively reported in Late Neoproterozoic/Early Palaeozoic time during formation of the East-African-Antarctic orogen (EAAO). Metamorphic data acquired from the Pan-African orogen of central Dronning Maud Land (cDML) are compared with data from northern Mozambique. The metamorphic rocks of cDML are characterised by Opx±Grt-bearing gneisses and Sil+Kfs-bearing metapelites which indicate medium-P granulite-facies metamorphism. Peak conditions, which are estimated to 800-900ºC at pressures up to 1.0 GPa, were followed by near-isothermal decompression during late Pan-African extension and exhumation. Granulite-facies lithologies are widespread in northern Mozambique, and Grt+Cpx-bearing assemblages show that high-P granulitefacies conditions with PT reaching 1.55 GPa and 900ºC were reached during the Pan-African orogeny. Garnet is replaced by symplectites of Pl+Opx+Mag indicating isothermal decompression, and the subsequent formation of Pl+amphibole-coronas suggests cooling into amphibolite facies. It is concluded that high-T metamorphism was pervasive in EAAO in Late Neoproterozoic/Early Paleozoic time, strongly overprinting evidences of earlier metamorphic assemblages.
Keywords: Dronning Maud Land; geologi

Marine-sedimentary geology - Kuhn, Gerhard; Hillenbrand, Claus-Dieter; Hass, Christian; Lensch, Norbert; Forwick, Matthias; Daniel, Kristin; Kober, Martin; Krüger, Stefan; Petitat, Manuel; Veit, Andreas (The Expedition ANT-XXIII/4 of the Research Vessel Polarstern in 2006, 2007)
Dynamic behaviour of the West Antarctic ice sheet in the Amundsen Sea Embayment during the later quaternary climatic cycles, pliocene to quaternary palaeoceanography in the Southwest Pacific, and holocene climate history of Maxwell Bay, King George Island.
Keywords: Sørishavet; havnivåstigning; innlandsis; klimaendringer; marin geologi; oseanografi

Kap. 4. Is og snø smelter. Kap. 5. Øyer og lavland kan drukne - Mathismoen, Ole; Ulvestad, Knut Ola (bildered.); Lie, Maya (bildered.) (Klima : hva skjer?, 2007)
Keywords: Antarktis; Sørishavet; drivhuseffekten; global oppvarming; havnivåstigning; klimaendringer